Satellite remote sensing for assessment of irrigation system performance: a case study in India - Thiruvengadachari, S.; Sakthivadivel, Ramaswamy (International Irrigation Management Institute, 1997)
Describes the use of satellite remote sensing and geographic information system techniques to obtain information on primary agricultural productivity and irrigation system performance in a large rice irrigation system in India. Discusses the potential and cost-effectiveness of SRS techniques for making inventories and monitoring agricultural productivity.